Living the Examined Life in the Antebellum North, and in the Post–World War II United StatesThe Grimké Sisters from South Carolina: Pioneers for Women's Rights and Abolition, by Gerda Lerner. Issue 5 (3rd December 2018) - Jones, Jacqueline
Abstract: This essay offers an appreciative reappraisal of Gerda Lerner's The Grimké Sisters from South Carolina: Pioneers for Women's Rights and Abolition, a dual biography published more than half a century ago. Jones gives an overview of the author's distinguished career and, summarizing the book, argues that its enduring appeal can be traced to several factors—Lerner's extensive archival research, her skill as a storyteller, the book's wide-ranging themes related to the antebellum United States, and the drama inherent in the sisters' public and private lives. The daughters of a wealthy Charleston, South Carolina, slaveholder, both Sarah and Angelina moved north in the 1820s. There they became prominent speaker-activists on behalf of abolitionism and the rights of women. Since The Grimké Sisters from South Carolina was published, scholars have enhanced our understanding of many of the themes in the book, while continuing to draw upon it for their own research on any number of topics—antebellum slaveholding households, reform, and notions of citizenship, among others. Lerner's sensitive rendering of the sisters' struggles is as moving and thought-provoking a piece of scholarship today as it was when it was written five decades ago.